Type and distribution of indomethacin-induced lesions in the gastrointestinal tract of rat - Kuneš, Martin; Květina, Jaroslav; Bureš, Jan (Neuro-endocrinology letters, 2009)
OBJECTIVES: The therapy with non-steroidal anti-inflammatory drugs (e.g. indomethacin) is often accompanied with adverse effects in gastrointestinal tract. Aim of this experimental study was to define the time range of the creation of indomethacin-induced gastrointestinal lesions in rat (for prospective study of potential probiotic therapy). The paper follows our previous experiments where the different gastrointestinal lesions were described in the pig (Kvetina et al. 2008) METHODS: Indomethacin (25mg/kg) was administered orally by a single application to rat (Wistar Han II, 200-250g). Six, 24, 48 and 72 hours after the indomethacin administration all parts of the gastrointestinal tract of six rats in each time interval were macroscopically and histologically examined. RESULTS AND CONCLUSION: The gradual development of lesions was observed 6 hours in stomach and 24-72 hours in the intestine after the indomethacin administration. Not only the gradual development of pathophysiological alterations was observed but also the reparative phase (in stomach). 24 hours seem to be advisable time suitable for the evaluation of the probiotics effect as a potential therapy) on the indomethacin-induced gastrointestinal lesions in rats. Sensitivity of the gastrointestinal tract to the pathological lesions development seems to be higher in rats in comparison to findings described in our previous experiments in pig (Kvetina et al. 2008). This adverts to interspecies differences in the manifestation and in the dynamics of the development of gastrointestinal lesions.
Keywords: Prospective Studies; Toxicity Tests; Anti-Inflammatory Agents, Non-Steroidal; prospektivní studie; zvířata; Rats; Administration, Oral; antiflogistika nesteroidní; Gastrointestinal Diseases; Time Factors; mužské pohlaví; Intestines; testy toxicity; Indomethacin; žaludek; Stomach; Rats, Wistar; časové faktory; aplikace orální; krysa rodu Rattus; potkani Wistar; střeva; Animals; gastrointestinální nemoci; Male; indomethacin